MENINGKATKAN PARTISIPASI AKTIF SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION SISWA KELAS X TPM 3 SMK PGRI 1 KOTA KEDIRI (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This research is motivated by the low active participation of students in class X TPM 3 at SMK PGRI 1 Kediri in Pancasila Education, attributed to conventional teaching methods that are less engaging. The study aims to identify the steps of the Group Investigation learning model that can enhance students' active participation, as well as how student learning activities with this model can improve their active participation. The method used is Classroom Action Research (CAR) conducted in two cycles, involving 37 students. Data were collected using an active student participation observation sheet. The results indicate that in Cycle I, the average student participation reached 63.51% (sufficient category), while in Cycle II it increased to 85.54% (very good category). The application of the Group Investigation model proved effective in significantly improving students' active participation, with 78% of students achieving the "Very Good" category in the second cycle. In conclusion, the Group Investigation model can significantly enhance students' active participation in Pancasila Education, creating a more interactive and meaningful learning environment.